Factors that lead to stagnation of total fertility rate (TFR) decline in Jakarta Province based on 2017 Indonesian demographic and health survey (IDHS) data - Windiany, Erina; Rahel, Tiarlin Lavida; Sugihanawati, Anah (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: The Total Fertility Rate (TFR) of 2017 IDHS data in Jakarta stagnated at 2.2, which has not yet reached the TFR target of 2.1. Objective: To investigate the variables associated with the stagnation of TFR decline in Jakarta based on the 2017 Jakarta IDHS data.Methods: Cross-sectional design, source of secondary data came from the 2017 IDHS fertility data of DKI Jakarta Province. Sample data of women of childbearing age, 883 samples. Independent variables: characteristics (age, education, occupation, decision maker), reproductive services (source of family planning services, media about family planning) and reproductive behavior (age at first active sexual intercourse, family planning method, use of health insurance, opinion about number of children). Data analysis was conducted up to the multivariate.Results: There was an association between age (p=0.000), education (p=0.028), decision maker (p=0.000), source of family planning services (p=0.000), age of sexual activity (p=0.008), contraceptive method (p=0.000) and opinion on number of children (p=0.000) with stagnation of TFR decline. Multivariate analysis: The OR value (2.331) was highest for the variable opinion about having more than two children.Conclusion: Factors that lead to stagnation of TFR decline in Jakarta were most at risk in the variable women of child bearing age opinion about having more than two children. Education is needed to raise awareness about the perception of ideal child value